Freshly excavated fossil bones are best for amplification of ancient DNA - Pruvost, Mélanie (National Academy of Sciences, 2007)
Despite the enormous potential of analyses of ancient DNA for phylogeographic studies of past populations, the impact these analyses, most of which are performed with fossil samples from natural history museum collections, has been limited to some extent by the inefficient recovery of ancient genetic material. Here we show that the standard storage conditions and/or treatments of fossil bones in these collections can be detrimental to DNA survival. Using a quantitative paleogenetic analysis of 247 herbivore fossil bones up to 50,000 years old and originating from 60 different archeological and paleontological contexts, we demonstrate that freshly excavated and nontreated unwashed bones contain six times more DNA and yield twice as many authentic DNA sequences as bones treated with standard procedures. This effect was even more pronounced with bones from one Neolithic site, where only freshly excavated bones yielded results. Finally, we compared the DNA content in the fossil bones of one animal, a ≈3,200-year-old aurochs, excavated in two separate seasons 57 years apart. Whereas the washed museum-stored fossil bones did not permit any DNA amplification, all recently excavated bones yielded authentic aurochs sequences. We established that during the 57 years when the aurochs bones were stored in a collection, at least as much amplifiable DNA was lost as during the previous 3,200 years of burial. This result calls for a revision of the postexcavation treatment of fossil bones to better preserve the genetic heritage of past life forms.